The Landmark Series: Breast Conservation Trials (including oncoplastic breast surgery) - Margenthaler, Julie A.; Dietz, Jill R.; Chatterjee, Abhishek (Annals of surgical oncology, 2021)
Significant progress has been made in the treatment and outcome of breast cancer. Some of the most dramatic strides have been in the surgical management of breast cancer. Breast-conserving therapy (BCT), including wide local excision of the tumor followed by irradiation, has become a standard treatment option for women with early-stage invasive breast cancer. Large cooperative group trials have contributed to the paradigm shift from mastectomy to BCT. This review reports the landmark BCT trials that provided the data for current surgical practices. The review also describes the body of literature contributing to the increasing use of oncoplastic techniques for patients undergoing BCT.